Influence du numérique sur la coordination entre acteurs dans les filières pastorales au Sénégal - Sow, A.-P.; Ba, Baba; Ferrari, S.; Cesaro, J.-D. (2024)
The pastoral sectors in Senegal have witnessed the emergence of new forms of information circulation and coordination in recent years, driven by the use of digital technology. The stakeholders in these sectors, who have been equipped with mobile phones since the beginning of the 21st century, are now beginning to use smartphones and their features, including voice communication, sharing images and videos within discussion groups, and transferring money. These uses address specific needs of pastoral systems, particularly related to the mobility of herds and the distance between stakeholders. This technological transition in pastoral sectors has attracted the interest of numerous institutional actors such as governments, civil society organizations, and businesses, all eager to better control this economy or develop commercial relationships with herders. These digital practices seem to have the potential to better link supply and demand. However, the adoption of these new digital technologies remains limited to a small number of actors, primarily urban or intermediary, potentially creating a divide between highly connected livestock farmers and others who are less connected.